Efficiency of mobile apps for monitoring and management of mental health - review article - Jędrzejewska, Barbara; Borycka, Aleksandra; Kotulska, Maria; Laskus, Paulina; Lichman, Martyna; Lubczyńska, Zuzanna; Potocka, Zofia; Przeradzki, Jakub; Rząd, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction and purpose Mobile health apps are becoming increasingly popular. Many of them deal with improving mental well-being. This work aims to determine the effectiveness of using self-help forms of mental health care using mobile phones. Material and Methods The literature on mobile applications for mental health was reviewed using the databases of PubMed and Google Scholar. State of knowledge Mental illness is a severe problem for a large part of society. There is often effective treatment for them, but access to health care resources is limited. There are many applications that offer users psychoeducation and elements of psychotherapy. Many studies have shown their effectiveness in treating depression, anxiety disorders and dealing with excessive stress. Some research papers show the usefulness of mobile services in coping with distorted body image in body dysmorphic disorder, as well as in controlling physical activity and sleep time in the case of insomnia. Some of the programs seem to be useful in the functioning of people suffering from bipolar affective disorder, but their effectiveness in this disease is limited and still being analyzed. Summary Mobile health applications for monitoring and improving mental health are a promising form of helping patients. Some of them have been proven to work, but more research is needed on specific programs. It is important to remember that apps are used to supplement treatment, and do not fully replace contact with psychiatrists and psychologists.